mantisGRID: A Grid Platform for DICOM Medical Images Management in Colombia and Latin America. - Garcia Ruiz, Manuel; Garcia Chaves, Alvin; Ruiz Ibañez, Carlos; Gutierrez Mazo, Jorge; Ramirez Giraldo, Juan; Pelaez Echavarria, Alejandro; Valencia Diaz, Edison; Pelaez Restrepo, Gustavo; Montoya Munera, Edwin; Garcia Loaiza, Bernardo; Gomez Gonzalez, Sebastian (Journal of Digital Imaging, 2011)
This paper presents the mantisGRID project, an interinstitutional initiative from Colombian medical and academic centers aiming to provide medical grid services for Colombia and Latin America. The mantisGRID is a GRID platform, based on open source grid infrastructure that provides the necessary services to access and exchange medical images and associated information following digital imaging and communications in medicine (DICOM) and health level 7 standards. The paper focuses first on the data abstraction architecture, which is achieved via Open Grid Services Architecture Data Access and Integration (OGSA-DAI) services and supported by the Globus Toolkit. The grid currently uses a 30-Mb bandwidth of the Colombian High Technology Academic Network, RENATA, connected to Internet 2. It also includes a discussion on the relational database created to handle the DICOM objects that were represented using Extensible Markup Language Schema documents, as well as other features implemented such as data security, user authentication, and patient confidentiality. Grid performance was tested using the three current operative nodes and the results demonstrated comparable query times between the mantisGRID (OGSA-DAI) and Distributed mySQL databases, especially for a large number of records.